Acute lymphoblastic leukemia presenting as cholestatic jaundice in a 7-year-old boy. (September 2019) - Ford, Jessica; Rainey, Shane; Hanson, Keith; Kendhari, Harleena
This is a case of a 7-year-old boy with acute lymphoblastic leukemia presenting with cholestasis and elevated transaminase levels. Acute lymphoblastic leukemia is the most common malignancy in children and can have variable presenting clinical manifestations. However, cholestasis is less commonly encountered in the pediatric population and can be a diagnostic challenge. We present a case of a 7-year-old boy discovered to have elevated transaminase levels while undergoing an evaluation for motor tics, which subsequently progressed to cholestasis and acute liver failure secondary to acute lymphoblastic leukemia. He demonstrated marked improvement after induction therapy and is in clinical remission. Clinicians should be ever mindful of the potentially unique presentations of childhood leukemia.